PENGARUH WORK OVERLOAD DAN STRES KERJA TERHADAP INTENSI TURNOVER STUDI DI PT. XY - Veronica, Imelda (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstract: Turnover Intention is a big problem for a company its causesignificant impact on a company. one of the factors that influence it iswork stress and work overload. Companies must understand thiscorrectly so that prevention can be done. The research respondentswere limited to PT XY employees. This type of quantitative researchand instruments used are questionnaires. Data validity is obtainedthrough validity and reliability. Based on the results of the study foundwork overload and work stress have a positive and significant effect onturnover intention.Keywords: influence, work overload, work stress, turnover